SEMIOTIC ANALYSIS ON KIMETSU NO YAIBA MOVIE POSTERS - Andriani, Diyah Iis; Anti, Dewi Yuli (BASIS (Bahasa dan Sastra Inggris), 2022)
This research is aimed to explain the types of semiotic signs and symbols, the denotations and connotations meaning of signs and symbols found in the posters on Kimetsu no Yaiba. The researchers use the descriptive qualitative method to identify, analyze, and explain the signs and symbols in Kimetsu no Yaiba the movie posters. The theory used by the researchers in carrying out this research is the theory of Dyer (2009) to analyze the types of semiotic signs and symbols. In addition, Barthes’ theory (1983) is used to analyze the denotation and connotation meaning. The data in the analysis chapter are taken from pictures, words, expressions, and colors in four posters on Kimetsu no Yaiba the Movie. The results of this research show that there are 26 symbols consisting of both verbal and visual signs, each of which is viewed from the meaning of denotation and connotation. Further, after translating the symbols and signs using the theory of Dyer (2009) and Barthes (1983), it is found that the meanings revealed give a teaser or clue about the story which tells about the journey in carrying out missions.